Gross Motor Skills: Outbound Activities in Elementary Students - Lutfi Nur; Rosarina Giyartini; Sumardi Sumardi (STKIP Muhammadiyah Kuningan, 2020)
This study aims to determine the development of gross motor skills of elementary school students through outbound game activities. The research method used was one group pretest-posttest design to find out the motor development of students. Twenty Elementary School students at Tasikmalaya Laboratory in grade 1 were involved in this study. Data collection instruments used were structured observation, field notes, and documentation regarding students' gross motor skills. The results show the highest percentage increase in gross motor skills of students by 41% in the aspect of flexibility and the lowest increase in the aspect of children's ability to throw a ball with a percentage increase in 33%. The conclusion of this study is that outbound activities implemented in the learning process can improve students' gross motor skills.